Respon Teologis Terhadap Dampak Pandemik Coronaviruses Disease 2019 - Sandra Christina Sahensolar; Simon Simon (Manna Rafflesia, 2021)
The coronavirus disease 2019 (covid-19) pandemic has had a huge impact on human life. This study highlights how the theological response to the impact caused by covid-19, both in the context of religious and economic rituals. The method used by the researcher is a qualitative method with a literature study approach. The results of the description in this article suggest that the covid-19 pandemic has caused all global communities and various aspects to be seriously affected by this outbreak, In this outbreak, the world economy has slumped, many people have died due to covid-19, and the space for religious rituals has been restricted. In the context of Christian theology, this pandemic can be indicated as the fulfillment of Bible prophecy as John's prophecy in the book of Revelation. Theologically, this plague is a punishment for humans who are willing to exploit nature. This epidemic is also a form of God's warning in the midst of increasingly corrupted human morality, which eases sinful acts without heeding the truth of God's word. This study concludes that the theological response to the covid-19 pandemic is to be more vigilant spiritually and build a life that glorifies God.